Relación entre Antecedente Empresarial Familiar y el Emprendimiento de Micro y Pequeñas Empresas - Chávez-Márquez, Irma Leticia; Álvarez-Loya, Liliana; Rosas-García, Blanca Margarita; Sánchez-Acosta, Luis Raúl (European Scientific Journal, ESJ, 2017)
The objective of the research was to determine the relationship between the family business background and the entrepreneurship of micro and small enterprises. A total census of 123 companies registered in the Business Incubator of the Facultad de Contaduría y Administración of the Universidad Autónoma de Chihuahua in Chihuahua, Mexico, was carried out. The research was descriptive and exploratory; using the analyticalsynthetic method, with a transectional design, performed between April and June 2016. The dependent variable was the generation of companies and the independent variable was to have a family business background. The main results indicate that the majority of entrepreneurs with companies in operation, have a family business background. However, it is not decisive to not have a relative with a company, and other factors can also influence the entrepreneurship of new companies, among which may be the support provided by the business incubator.